A Letter from the Airport - Mun, Chŏng-hŭi, 1947- (Book collections on Project MUSE., 2018)
This pocket-sized paperback is one of the twenty-four titles published for 2017 Hong Kong International Poetry Nights. The theme of IPHHK2017 is "Ancient Enmity". IPNHK is one of the most influential international poetry events in Asia. From 22-26 November 2017, over 20 invited poets from various countries will be in Hong Kong to read their works based on the theme "Ancient Enmity." Included in the anthology and box set, these unique works are presented with Chinese and English translations in bilingual or trilingual formats.